Triazole fungicides in soil affect the yield of fruit, green biomass, and phenolics production of Solanum lycopersicum L - Jakl, Michal; Kovač, Ishak; Ćavar Zeljković, Sanja; Jaklová Dytrtová, Jana (Food chemistry, 2021)
A part of the fungicides used in foliar treatment penetrates into the soil. This study describes changes in the bioavailability of (essential) elements in soil, fructification, the amount of green biomass and the production of phenolic compounds related solely to the presence of triazoles (penconazole and cyproconazole) in soil, injected as a single compound or their mixture. The triazoles presence has substantially affected the bioavailability of Fe, Cu and Zn in soil. The amount of green biomass has significantly decreased, whereas the chlorophylls a and b have not been affected. As a potential mark of plant stress, the fruits of the treated variants are significantly bigger. The content of phenolics in tomato peel (e.g. quercetin, quercitrin, hesperidin, naringin, and chlorogenic, salicylic and p-coumaric acid) has been quantified. The biggest changes (increase/decrease) have been observed in the contents of p-coumaric and chlorogenic acid, quercetin and quercitrin.
Keywords: Solanum lycopersicum; Fungicides, Industrial; Cyproconazole; Chlorogenic acid; průmyslové fungicidy; biologická dostupnost; půda; fenoly; Triazoles; biomasa; Biological Availability; Penconazole; P-coumaric acid; Phenols; ovoce; Fruit; triazoly; Soil; Biomass; Element bioavailability; Plant stress; Quercetin